Necroptosis–senescence crosstalk in tubulointerstitial fibrosis: the mtDNA–cGAS–STING–PFKFB3 axis as a metabolic bridge - Donghui Wang; Hongxiang Zheng; Xinyue Zhang; Chenghua Zhang; Dandan Zhao; Shuqi Min; Shenju Wang (Frontiers in Medicine, 2026)
Background Chronic kidney disease progresses irreversibly toward tubulointerstitial fibrosis. Although renin-angiotensin system inhibitors and sodium-glucose cotransporter 2 inhibitors slow progression, they cannot block or reverse fibrosis. Recent work shows that necroptosis and cellular senescence in tubular epithelial cells are not independent events; they form a dynamically evolving continuum through the mitochondrial DNA-cyclic GMP-AMP synthase-stimulator of interferon genes-interferon regulatory factor 3-6-phosphofructo-2-kinase/fructose-2,6-bisphosphatase 3-glycolysis axis. Methods We conducted a narrative review of peer-reviewed literature at the intersection of necroptosis, cellular senescence, and renal tubulointerstitial fibrosis. Systematic searches of PubMed/MEDLINE, Web of Science, and Embase were performed on 15 July 2026 using Medical Subject Headings terms and free-text keywords; evidence was classified using a pragmatic taxonomy ( in vitro , in vivo , phase I/II, and post hoc /subgroup analyses). Results Necroptotic tubular epithelial cell death releases mitochondrial DNA that activates cyclic GMP-AMP synthase-stimulator of interferon genes-interferon regulatory factor 3-dependent 6-phosphofructo-2-kinase/fructose-2,6-bisphosphatase 3 transcription, driving glycolytic reprogramming that sustains and amplifies the senescence-associated secretory phenotype through histone H4 lysine 12 lactylation. Senescence-associated secretory phenotype factors activate interstitial fibroblasts and reciprocally prime adjacent tubular epithelial cells for necroptosis, creating a self-amplifying loop. Existing targeted strategies—inhibitors of receptor-interacting serine/threonine-protein kinase 1, senolytics, 6-phosphofructo-2-kinase/fructose-2,6-bisphosphatase 3 blockers, and multi-target traditional Chinese medicine—show preclinical efficacy but face translation barriers arising from target selectivity, biomarker absence, and ill-defined therapeutic windows. Conclusion Future antifibrotic strategies should shift from single-molecule inhibition to network remodeling, using chronology-based combination therapy tailored to disease stage and guided by dynamic biomarkers.